Airborne exposure limits for chemical and biological warfare agents: is everything set and clear? - Sabelnikov A; Zhukov V; Kempf CR (International Journal of Environmental Health Research, 2006)
Emergency response strategies (guidelines) for biological, chemical, nuclear, or radiological terrorist events should be based on scientifically established exposure limits for all the agents or materials involved. In the case of a radiological terrorist event, emergency response guidelines (ERG) have been worked out. In the case of a terrorist event with the use of chemical warfare (CW) agents the situation is not that clear, though the new guidelines and clean-up values are being generated based on re-evaluation of toxicological and risk data. For biological warfare (BW) agents, such guidelines do not yet exist. In this paper the current status of airborne exposure limits (AELs) for chemical and biological warfare (CBW) agents are reviewed. Particular emphasis is put on BW agents that lack such data. An efficient, temporary solution to bridge the gap in experimental infectious data and to set provisional AELs for BW agents is suggested. It is based on mathematically generated risks of infection for BW agents grouped by their alleged ID50 values in three categories: with low, intermediate and high ID50 values.